PENINGKATAN KAPASITAS POKDARWIS KARANG MERAH DESA AIR ANYIR KABUPATEN BANGKA - Zakia Ayu Lestari; Pusparini, Marissa; Utama, Muhammad Arinda Unigraha (JURNAL MATA PARIWISATA, 2024)
This study aims to examine the capacity-building efforts of the Karang Merah Tourism Awareness Group (Pokdarwis) in managing and developing the Temberan Beach tourist destination in Air Anyir Village, Bangka Regency. Using a descriptive qualitative method, this research explores the existing conditions of Pokdarwis and Temberan Beach, the challenges faced, and the capacity-building strategies and programs that have been and need to be implemented. The results show that Pokdarwis Karang Merah has played a significant role in the development of Temberan Beach, but still faces major challenges related to limited human resource capacity, funding, and coordination with stakeholders. Various capacity-building programs have been conducted, including tourism training, tourism product development workshops, comparative studies, management assistance, English language training, and environmental awareness education. These programs have begun to show positive results, evident from the improvement in service quality and the emergence of innovations in tourism attraction development. This study concludes that Pokdarwis capacity building is an ongoing process that requires support and cooperation from various parties. Recommendations are provided for Pokdarwis, local government, academics, the private sector, and local communities to support sustainable capacity-building efforts for Pokdarwis.